Genetic diversity, population structure and DNA fingerprinting of abaca (Musa textilis Nee) - Yllano, Orlex B.; Lalusin, Antonio L.; Castro, Sheryl D.; Laurena, Antonio C.; Tecson-Mendoza, Evelyn Mae (2011)
Abaca, an indigenous fiber crop, is a major export commodity of the country. Assessing the genetic diversity of abaca is a prerequisite to a successful breeding program. Using microsatellite markers, the genetic diversity of abaca in Luzon, Viasayas and Mindanao was determined to be highly diverse (I = 0.67). These variations present in abaca population are needed in widening the genetic background of the species, thereby, providing a wide selection of parents for abaca breeding programs. The genetic structure of abaca population is considered as genetically heterogeneous with 94% variability within population (AMOVA). Principal component analysis revealed sharing of alleles in three populations. Distance matrix analysis clustered abaca genotypes from Luzon, Visayas and Mindanao into three big groups and six small groups. This study also optimized SSR markers with high polymorphism information content (PIC) value (0.48 to 0.79). A combination of SSR markers that can differentiate T genome (textilis), B genome (balbisiana) and A genome (acuminata) of the genus Musa was also identified. Using these markers, some of the duplicate accessions of abaca in the gene bank were recognized. Likewise, these SSR markers can distinguish susceptible, tolerant and resistant gen to abaca bunchy top disease (AbBTD) which are crucial for marker-assisted breeding for AbBTVD resistance trait. These results are useful for abaca varietal identification, germplasm characterization, marker-assisted selection, and for the development of DNA-based diagnostic kit for AbBTV.
Keywords: Abaca; genetic diversity; DNA fingerprinting; Plant breeding